'Am I anorexic?': weight, eating and discourses of the body in online adolescent health communication - Mullany, Louise; Smith, Catherine; Harvey, Kevin; Adolphs, Svenja (Equinox Publishing, 2015)
This article explores the communicative choices of adolescents seeking advice from an internet-based health forum run by medical professionals. Techniques from the disciplines of sociolinguistics and corpus linguistics are integrated to examine the strategies used in adolescents’ health questions. We focus on the emergent theme of Weight and Eating, a concern which features prominently in adolescents’ requests to medical practitioners. The majority of advice requests are authored by adolescent girls, with queries peaking at age 12. A combined quantitative and qualitative analysis provides detailed insights into adolescents’ communicative strategies. Examinations of question types, register and a discourse-based analysis draw attention to dominant discourses of the body, including a ‘discourse of slenderness’ and a ‘discourse of normality’, which exercise negative influences on adolescents’ dietary behaviours. The findings are of applied linguistic relevance to health practitioners and educators as they provide them with access to adolescents’ health queries in their own language.